2022
DOI: 10.1101/2022.11.05.515289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multifunctional LysM effector ofBotrytis cinereacontributes to plant infection

Abstract: LysM effectors are suppressors of chitin-triggered plant immunity in biotrophic and hemibiotrophic fungi. Their role in necrotrophic fungi is unclear as these last are known to activate plant defenses and induce cell death. To characterize the role of the BcLysM1 gene encoding a putative LysM effector in the necrotrophic fungus Botrytis cinerea, its expression was followed by transcriptional fusion and by RT-qPCR in planta. Two tagged-recombinant proteins were produced, and two independent deletion strains wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…This study also showed up-regulation of the BcLysM1 gene exclusively in infection cushions in the early phase of infection, and demonstrated an additional role for the BcLysM1 effector in adhesion to the host besides the chitin-binding feature that is commonly shared among fungal LysM effectors (Crumière et al, 2022). Additionally, the agar plugs containing fungal hyphae are likely to contain CDIPs and phytotoxic SMs that have been produced and accumulated in the pre-culture (where the agar plugs are excised from), which could boost the fungal infection from the very early phase of the interaction.…”
Section: Inoculation Conditions Dramatically Affect Botrytis Disease ...supporting
confidence: 58%
See 1 more Smart Citation
“…This study also showed up-regulation of the BcLysM1 gene exclusively in infection cushions in the early phase of infection, and demonstrated an additional role for the BcLysM1 effector in adhesion to the host besides the chitin-binding feature that is commonly shared among fungal LysM effectors (Crumière et al, 2022). Additionally, the agar plugs containing fungal hyphae are likely to contain CDIPs and phytotoxic SMs that have been produced and accumulated in the pre-culture (where the agar plugs are excised from), which could boost the fungal infection from the very early phase of the interaction.…”
Section: Inoculation Conditions Dramatically Affect Botrytis Disease ...supporting
confidence: 58%
“…Choquer et al (2021) reported that genes related to the production of SMs, cell death inducing proteins and cell wall-degrading enzymes, were up-regulated in infection cushions in vitro and in planta. A recent study reported that a ∆BcLysM1 mutant displayed a lower disease incidence and retarded expansion of the secondary lesions only when the bean leaves were inoculated with mycelial plugs, while the same mutant was similarly virulent as the WT fungus when inoculated with conidia (Crumière et al, 2022).…”
Section: Inoculation Conditions Dramatically Affect Botrytis Disease ...mentioning
confidence: 99%
“…Further analyses showed that inhibition of cell death and PTI by the BcCrh4 75–126 fragment was dose‐dependent, suggesting that both epitopes compete on the same target. This mode of action resembles the sequestration of chitin oligomers and prevention of PTI by the Cladosporium fulvum LysM‐domain Ecp6 effector (De Jonge et al, 2010) and B. cinerea BcLysM1 putative LysM effector (Crumiere et al, 2022). The two domains probably compete for the same plant target since co‐infiltration of BcCrh4 75–126 with BcCrh4 22–41 and suppresses the induction of cell death and plant immune responses.…”
Section: Discussionmentioning
confidence: 93%